Understanding the long-term impacts of burn on the cardiovascular system. Issue 2 (March 2016) - Duke, Janine M.; Randall, Sean M.; Fear, Mark W.; Boyd, James H.; Rea, Suzanne; Wood, Fiona M.
Highlights: Burn is associated with increased admissions for circulatory diseases. Burn increases risk of first time admissions for ischaemic heart disease. Burn increases risk of first time admissions for cerebrovascular disease. Burn increases risk of first time admissions for heart failure. Burn increases long-term mortality caused by circulatory system diseases. Abstract: Background: Whilest the most obvious impact of burn is on the skin, systemic responses also occur after burn that lead to wide-spread changes to the body, including the heart. The aim of this study was to assess if burn in mid-aged and older adults is associated with increased long-term admissions and death due to diseases of the circulatory system. Methods: A population-based longitudinal study using linked hospital morbidity and death data from Western Australia was undertaken of adults aged at least 45 years when hospitalized for a first burn ( n = 6004) in 1980–2012 and a frequency matched non-injury comparison cohort, randomly selected from Western Australia's electoral roll ( n = 22, 673). Crude admission rates and cumulative length of stay for circulatory diseases were calculated. Negative binomial and Cox proportional hazards regression modelling were used to generate incidence rate ratios (IRR) and hazard ratios (HR), respectively. HR was used as a measure of the mortality rate ratio (MRR). Results: After adjustment for demographic factors and pre-existing health status, the burn cohort had 1.46 times (95% confidence interval (CI): 1.36–1.56) as many admissions and almost three times the number of days in hospital with a circulatory system diagnosis (IRR, 95%CI: 2.90, 2.60–3.25) than the uninjured cohort for circulatory diseases. The burn cohort had higher admission rates for ischaemic heart disease (IRR, 95%CI: 1.21, 1.07–1.36), heart failure (IRR, 95%CI: 2.29, 1.85–2.82) and cerebrovascular disease (IRR, 95%CI: 1.57, 1.33–1.84). The burn cohort was found to have increased long-term mortality caused by circulatory system diseases (MRR, 95%CI: 1.11, 1.02–1.20). Conclusions: Findings of increased hospital admission rates, prolonged length of hospital stay and increased long-term mortality related to circulatory system diseases in the burn cohort provide evidence to support that burn has long-lasting systemic impacts on the heart and circulation.